Predicting Tanjung Piai Coastline Changes Using Digital Shoreline Analysis System Method: Impact of Indonesia's Maritime Security - Aris, Tomi; Mamahit, Desi Albert; Ras, Abdul Rivai; Widodo, Ari (Applied Information System and Management (AISM), 2022)
Tanjung Piai, Malaysia Coastline changes are caused by abrasion and accretion processes triggered by intensive human activities in coastal areas. A coastline change will bring the potential for conflict and security threats to maritime countries, such as Indonesia. Monitoring shoreline changes is essential for studying coastal dynamics, protecting the coastal environment, and developing the coastal environment. This study aims to determine the changes of Tanjung Piai, Malaysia Coastline with Digital Shoreline Analysis System method and the effect on Indonesia's maritime security. The type of data used in this research is secondary data. This study shows that the Coastline changes along the West Coast of Tanjung Piai, Malaysia tend to be significant from year to year. Prediction the coastline that directly faced the Malacca Strait will experience accretion, while it will experience abrasion in the east. The highest accretion on transect 2, namely Sungai Permas Kechil of 19m/year with a distance of 600 meters. It was found that the influence of changes in the coastline of Tanjung Piai, Malaysia, on maritime security was seen from four aspects, namely aspects of sea power, marine safety, blue economy, and human security